Gastronomy Museums as Sustainable Hangouts in Gastronomy Tourism: A Gastronomy Museum Proposal for Gümüşhane City, Turkey - Akyürek, Suat; Erdem, Barış (Turizam, 2019)
Abstract The changes occur each passing day in demands and expectations of individuals participating to tourism movements lead to formation of new market fields in tourism industry. In this context, gastronomy tourism is regarded as one of the new trends in international tourism. Having hosted a large number of civilizations throughout the history, Turkey is accepted today as one the countries having the richest cuisines in the world. However, the efforts to transfer that gastronomic diversity to future generations are still limited in Turkey. In this study, gastronomy museums were focused on and a gastronomy museum was suggested to be established for Gümüşhane province. It is expected that the determinations revealed in the study will be a model also for other regions of Turkey and lead the way to transfer the gastronomic assets of Turkey to future generations. Keywords: Sustainable Tourism, Gastronomy, Gastronomy Museums, Gümüşhane City.